Studying agronomic characters in new millet accessions from the VIR collection at Yekaterinino Experiment Station of VIR - T. V. Kulemina (Труды по прикладной ботанике, генетике и селекции, 2021)
Background. Adding new plant varieties to the VIR collection is an important effort to preserve the diversity of worldwide bioresources. The millet collection at VIR is formed through the study of acquired accessions, aimed at identification of biological features that have emerged under certain conditions. Such germplasm may be recommended for use in breeding practice. Studying new accessions makes it possible to predict long-term development of the collection.Materials and methods. The study was carried out at Yekaterinino Experiment Station of VIR, Tambov Province, in 2017–2019. New millet accessions added to the VIR collection served as the research material. The study was based on the descriptors and guidelines for Panicum miliaceum L. developed at VIR.Results and conclusions. An assessment was made for such agronomic characters as the growing season, plant height, grain size, grain yield, and resistance to bacteria. The identified accessions exceeded the reference (cv. ‘Gorlinka’) in a number of traits. Earliness was observed in k-10479 (‘Dozh’), k-10481 (‘Zapadnoye’), k-10324, k-10325, k-10478 (‘Nizhnevolzhskoye’), k-10275 (‘Kvartet’), k-10306 (‘Volga 59’), k-10322 (‘Soyuz’), k-10473 (‘Yarkoye 120’), and k-10474 (‘Kavkazskiye zori’). Low plant height was recorded for k-888, k-10324, k-10306, k-10474, k-10479, k-10326, k-10481, and k-10480 (‘Kamyshenskoye’). Large grain size was shown by k-888, k-10325, k-10306, k-10324, k-10479, k-10475 (local), k-10322, k-10473, k-10480, and k-10481. High grain yields under the conditions of the Central Black Earth Region of Russia were demonstrated by the accessions from Belarus (cv. ‘Zapadnoye’, k-10481) and from Chelyabinsk Province (local cultivar, k-888). Medium and strong resistance to bacterial pathogens was observed in k-888, k-10275, k-10473, k-10474, k-10324, and k-10325. The selected accessions can serve as source material for the development of new millet cultivars.